Quantitative investigation of the fragmentation process and defect density evolution of oxo-functionalized graphene due to ultrasonication and milling. (January 2016) - Halbig, Christian E.; Nacken, Thomas J.; Walter, Johannes; Damm, Cornelia; Eigler, Siegfried; Peukert, Wolfgang
Abstract: In the view of technical and medical applications we examined the effect of ultrasonication and ball milling of oxo-functionalized graphene bearing an almost intact carbon lattice (oxo-G) with respect to the lateral flake size reduction and defect formation in the carbon lattice for the first time. The energy input was screened for both methods and quantitative changes in lateral flake size distribution were characterized in solution by analytical ultracentrifugation (AUC) supported by atomic force microscopy (AFM). For the first time, we applied statistical Raman spectroscopy to reliably evaluate the formation of lattice defects with processing time. Surprisingly, the density of lattice defects remains unaffected with energy inputs below a limiting threshold. Furthermore, for both processing techniques, the size reduction scales with the energy input according to a power law function, which is well known for emulsification and mechanical comminution processes. With the results of this study it is possible to precisely predetermine the lateral size of flakes of oxo-G upon sonication or milling processing, preserving the carbon lattice. Understanding this controlled formation of oxo-G flakes enables target oriented technical, medical and electronic applications with tailored properties.